SOLUTION
Given the question in the question tab, the following are the steps to find the equation
Step 1: Write the equation of the initial line and get the slope by comparing with the general line equation.
![\begin{gathered} y=mx+c \\ \text{where the coefficient of }x\text{ is the slope (m)} \\ y=(4)/(3)x+1 \\ m=(4)/(3) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/tf6sohcssdris8b0egr9ghvebuxf59lfrb.png)
Step 2: Get the slope of the perpendicular line
The slopes of two perpendicular lines are negative reciprocals of each other. This means that if a line is perpendicular to a line that has slope m, then the slope of the line is -1/m.
![\begin{gathered} m=(4)/(3) \\ m_{\text{perpendicular}}=-(1)/((4)/(3)) \\ m_{\text{perpendicular}}=-1*(3)/(4) \\ m_{\text{perpendicular}}=-(3)/(4) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/n2yjs2n2ukjrlkmqxwqzkpxpfgyckxz1p7.png)
Step 3: Get the y-intercept of the perpendicular line using the general equation of a line
![\begin{gathered} y=mx+b \\ (x,y)=(-7,-2),m=-(3)/(4) \\ -2=-(3)/(4)(-7)+b \\ -2=(21)/(4)+b \\ b=-2-(21)/(4) \\ b=-(8)/(4)-(21)/(4) \\ b=(-8-21)/(4) \\ b=-(29)/(4) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/meu0tq3w5sptd42buk6uj10jt2z61de8ab.png)
Step 4: We compute the final equation of the line perpendicular to y=4/3x+1 through point (-7,-2)
![\begin{gathered} y=mx+b \\ y=-(3)/(4)x+(-(29)/(4)) \\ y=-(3)/(4)x-(29)/(4) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ge3hg924qrzohtlj53fwjj72dvi0wgg7cm.png)
Hence, the equation of the line perpendicular to y=4/3x+1 through point (-7,-2) is:
![y=-(3)/(4)x-(29)/(4)](https://img.qammunity.org/2023/formulas/mathematics/college/svo68t3o2lr9p2yupuxaxchifjhlls457y.png)